KARAKTERISASI MORFOLOGI DAN ANATOMI AKSESI MANGGA DODOR (Mangifera sp.) DI KECAMATAN SINDUE KABUPATEN DONGGALA - Kabir, Kasran; Adelina, Enny; Maemunah, Maemunah (AGROTEKBIS, 2017)
Mango (Mangifera indica), is a fruit that comes from India, it has many varieties. Mangoes are generally marketed in the form of fresh, both for domestic and export purposes. The objectives of this study were to assess the accession mango dodor in Lembah Palu through characterization of morphological and anatomical Toaya and Lero Village Donggala District. The research method using accessibility method by observing plant morphology character was continued with characterization of diversity using cluster analysis using systat software 0.8. The results showed that there were several different accessions in each village in Sindue subdistrict based on morphological and anatomical characteristics.The different accessions in Toaya Village at a distance of 0.6 were obtained TF11, TF9, TF14. Lero village have different accessions, namely LR6, LR14, and LR13 and in Sindue sub-districts TF9, LR6, and LR15. Keywords: Anatomy, Mango, morphology.